Perencanaan Perkuatan Lereng Menggunakan Geoframe di Jalan Raya Dampit-Lumajang - Lafridha Alyazahari; Luthfi Amri Wicaksono; Dwi Nurtanto (Universitas Islam 45, 2022)
A Landslide is the movement of soil mass or rock constituents down the slope due to disturbance of soil stability. One of the factors that affect soil stability is the rainy season as happened in Sumberwuluh Village, Candipuro District, Lumajang Regency. The alternative used to stabilize the slope is by changing the slope geometry, then adding geoframe reinforcement. This study aims to determine the value of the factor of safety (SF) of unreinforced slopes, after changing the slope geometry, and after being given geoframe reinforcement. The method used in analyzing slope stability is the Ordinary/Fellenius method. The results of the calculation of slope stability without reinforcement using the Rocscience Slide software obtained a SF of 0.719, while the manual calculation obtained a SF of 0.7191. The two values ​​of the safety factor are less than 1.25, which means that landslides often occur. The results of the calculation of slope stability after changing the geometry of the slopes obtained a SF of 0.828 where the value is less than 1.25 which means that landslides often occur. The slopes that have been changed geometry are added with geoframe reinforcement. The results of the calculation of slope stability using geoframe reinforcement obtained a SF of 1.315 where the value is more than 1.25 which means that landslides are rare or slope in a safe condition.